Other cultures : aims, methods and achievements in social anthropology - Beattie, John (Routledge library editions. Anthropology and ethnography., 2004)
The first part of this book considers what kind of study social anthropology is, the types of questions social anthropologists ask and how they go about obtaining the answers. The second part discusses the more important fields in which social anthropologists have advanced our knowledge of other cultures: kinship and marriage, social order, economic relations and magical and religious institutions. The important theme of social change is also discussed. First published in 1964.